Affirmative Action as Earnings Redistribution: The Targeting of Compliance Reviews - Leonard, Jonathan S. (Journal of Labor Economics, 1985)
Affirmative action may be broadly conceived of as pursuing either the goal of reducing discrimination or that of redistributing jobs and earnings. I attempt to infer the ends of affirmative action policy by analyzing the historical record of enforcement. Optimal enforcement strategies are developed for both the antidiscrimination and the earnings redistribution models and then compared with new data on the actual targeting of affirmative action compliance reviews during the late 1970s. I find that establishments with very low proportions of minority or female workers are not significantly more likely to be reviewed, but that white-collar-intensive establishments are more likely to be reviewed. This indicates the shortcomings of the antidiscrimination model in explaining the OFCCP's behavior and suggests the potential usefulness of the earnings redistribution model.